A Study Ecological & Microbial Contamination on Rumetha river in Al-Muthana governorent - Ibtehal Aqeel, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Study included some physical and chemical properties of the river al-Rumetha where the observed high BOD5 values as a result of water exposure to pollutants also noted the high turbidity values during the months of study as a result of differing water levels. The other properties were within the standard limits. Results showed that the water pH is alkaline bicarbonates depending on the recorded values. The results of isolation and diagnosis in the study area the possibility to isolate and diagnose races bacterial many such as E.coli rate (62.5%) and Pseudomonas rate (58.3%) and Klebsiella & Shigella rate (22.2%) also diagnosed several genera of fungi, including Aspergillus by the emergence (20 , 02%) and the fungus Penicillium by the emergence of (19.6%) and Curvularia by (12.7%). showed bacteria resistant to two anti (GEN, AMI) while the other sensitive to antibiotics